Attitudes in Urban Landscape Aesthetics - Mohammad Mohazzab Tollab; Mehrdad Karimimoshaver; Hassan Sajadzadeh (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2018)
The beauty of the urban landscape includes different aspects and various criteria on which there are different attitudes and opinions. This research sought to identify these attitudes in the aesthetics of the urban landscape, especially at the micro-scale, i.e. urban space. At first, 61 assessment criteria were adjusted, then participants arranged them in a Q diagram based on the Q method. After gathering data, the correlation between subjects was evaluated by SPSS software with the Q-factor analysis method and 10 factors were extracted using principal components analysis and varimax rotation. Interpretation of these factors leads to 10 opinions: 1.Conservative and Traditional, 2.Naturalist and Meticulous, 3.Person-centered and Forward-looking, 4.Holistic and Reputation-oriented, 5.Pragmatic and Environment-centered, 6.Specialized and Architectural, 7.Nature-centered and Semantic, 8.Experience-oriented and Social, 9.Community-oriented and Practical, 10.Civil and Culture-centered. Moreover, multidimensional opinions and simultaneous consideration to different aspects of urban landscape aesthetics in most opinions unlike current imagination showed that most of the citizens not necessarily focus on subjective and perceptive aspects. On the other hand, gender differentiation was observed among opinions which can be related to type and amount of presence and experience of them in the city that leads to contradictory attitudes among them.